Ewald Banse : orientaliste et « géographe de l’âme » - Catherine Repussard (Recherches Germaniques)
This paper examines political views on Persia in the Weimar Republic of the 1920s. That era witnessed the emergence of a ‘geography of the soul’, combined with the idea of the ‘soul of peoples’, a legacy of political romanticism that echoed with the then fashionable concept of psychology of peoples (Völkerpsychologie). Geographers and orientalists strove to map out the ‘geography of the Persian soul’ alongside the ‘geography of the German soul’. Here the book Morgenland und Abendland. Landschaft Rasse Kultur zweier Welten (1926), by the atypical geographer and great popularizer of science Ewald Banse (1883-1953), is more specifically addressed. Banse attempted to trace the outlines of a Germano-Persian ‘imagined community’, in the sense of Benedict Anderson. Along with other German orientalists, he intended it to legitimize what he saw as the necessary cultural Germanization of the Orient, under the premise that cultural policy (Kulturpolitik) was the new form of territorial expansion (Raumpolitik).